INVESTIGATION OF DRY FRICTION PHENOMENA IN MECHANICAL SYSTEMS: THEORETICAL MODELING AND PRACTICAL APPLICATIONS (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This study provides a comprehensive analysis of the role of dry friction in mechanical systems, as well as its theoretical and practical aspects. Dry friction is considered as a complex contact phenomenon that occurs in the absence of a lubricating layer between contacting bodies, and its characteristics in both static and kinetic states are described. The main factors influencing the formation of friction force-surface topography, material properties, adhesion, and environmental conditions-are explained on a scientific basis. In addition, the study examines dry friction not only within the framework of the classical Coulomb model but also from the perspective of modern approaches, including contact mechanics and interfacial energy effects. The necessity of accounting for friction forces in determining the equilibrium of mechanical systems is substantiated, and methods for solving various types of static problems are presented. The theoretical principles are supported by practical problems, demonstrating their importance in improving the reliability and efficiency of mechanical systems.